Morphology of the Vieussens valve and its imaging in cardiac multislice computed tomography. (18th June 2019) - Żabówka, Anna; Hołda, Jakub; Strona, Marcin; Koziej, Mateusz; Krawczyk‐Ożóg, Agata; Jasińska, Katarzyna A.; Kuniewicz, Marcin; Lelakowski, Jacek; Hołda, Mateusz K.
Abstract: Introduction: To deliver accurate morphological descriptions of the Vieussens valve (VV) and to investigate whether this structure could be visualized using standard contrast‐enhanced electrocardiogram‐gated multislice computed tomography (MSCT). Methods: A total of 145 human autopsied hearts and 114 cardiac MSCT scans were examined. Results: The VV was observed in both study groups, however, the detection rate was significantly worse in the MSCT examination (18.4% in MSCT vs 62.1% in cadavers, P < .0001). The VV height was larger in MSCT patients (2.8 ± 1.2 vs 5.4 ± 1.7 mm; P < .0001). No significant difference was found in the measured distance between the VV and the coronary sinus ostium between the two separate subgroups (27.3 ± 9.5 vs 24.4 ± 5.8 mm; P = .18). In autopsied material the most frequent valve location was the anterior wall of the coronary sinus (43.3%); the same was observed in MSCT scans (71.4%). Conclusion: The VV is a common heart structure, present in over 60% of humans, located mainly on the anterior and superior circuit of the coronary sinus, with relatively high morphological variability. Large VVs, which pose a significant obstacle in catheterization procedures, may be visualized using standard‐protocol contrast‐enhanced cardiac MSCT.